114k views
3 votes
How do I solve this?

How do I solve this?-example-1
User KeyNone
by
7.1k points

1 Answer

3 votes

Answer:

(-6,1) (2,7)

Explanation:

y =x+5

y = x^2 +5x-7

Set the two equations equal since y=y

x+5 = x^2 +5x -7

Subtract x from each side

x-x+5 = x^2 +5x-x -7

5 = x^2 +4x -7

Subtract 5 from each side

5-5 = x^2 +4x -7-5

0 = x^2 +4x-12

Now we can factor the right side

What 2 numbers multiply to -12 and add to +4

6*-2 =-12

6-2 =4

0 = (x+6) (x-2)

Using the zero product property

x+6=0 x-2=0

x=-6 x=2

We need to find y for each value of x

y = x+5 y = x+5

y = -6+5 y = 2+5

y =1 y = 7

User Bossie
by
8.8k points